2019
DOI: 10.1111/cns.13129
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin disrupts vascular endothelial‐cadherin and leads to hydrocephalus via protease‐activated receptors‐1 pathway

Abstract: Summary Aims Previous studies indicated that intraventricular injection of thrombin would induce hydrocephalus. But how thrombin works in this process remains unclear. Since cadherin plays a critical role in hydrocephalus, we aimed to explore the mechanisms of how thrombin acted on choroid plexus vascular endothelium and how thrombin interacted with vascular endothelial‐cadherin (VE‐cadherin) during hydrocephalus. Methods There were two parts in this study. Firstly, rats received an injection of saline or thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…It is well known that 50μl of whole blood produces 13 to 18 units of thrombin [22] and intraventricular infusion of 5 units of thrombin caused high mortality in our preliminary experiments. Thus, the amount of thrombin in this current study was 3 unites in 50μl saline, the same as our previous study [2,3].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…It is well known that 50μl of whole blood produces 13 to 18 units of thrombin [22] and intraventricular infusion of 5 units of thrombin caused high mortality in our preliminary experiments. Thus, the amount of thrombin in this current study was 3 unites in 50μl saline, the same as our previous study [2,3].…”
Section: Discussionmentioning
confidence: 62%
“…Hydrocephalus is an independent risk factor of hemorrhage-associated morbidity [1]. Our previous study found that thrombin played a critical role in hydrocephalus [2,3]. Cerebrospinal fluid (CSF) is mainly produced in choroid plexus and absorbed in subarachnoid space, and the key point of hydrocephalus should be the changes in formation or absorption of CSF [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this special issue, Wan et al demonstrated that activation of epiplexus cells is associated with SAH‐ and thrombin‐induced hydrocephalus . The effect of thrombin in hydrocephalus development may be through protease‐activated receptor‐1 …”
mentioning
confidence: 99%